Upaya Meningkatkan Efektifitas Pola Napas Pada Pasien Fraktur Dislokasi Servikal Di RSOP Surakarta - Lusiana, Dina; , Fahrun Nur Rosid, S.Kep., Ns., M.Kes (2016)
Patients with cervical injury (cervical dislocation fraktur) some patient will exprience unstable spine injury can give high risk of injury cord, causing an actual problem or risk of ineffective breathing pattern and decreased cardiac output due to loss control of visceral organ. Deep breathing exercise is a breathing exercise with breathing techniques slowly and deep, using the diaphragma muscle, thus allowing abdoment and chest lifted slowly and swelled. The objective of the research paper is to understand nursing care for patients with a diagnosis cervical dislocation fracture and determine the effect of giving a deep breath of the patient with ineffectivess of breathing patterns in patient with cervical dislocation fracture. This research uses descriptive case study approach on Mr. HB by performing nursing care, ranging for assessment, intervention, diagnose of nursing implementation, and evaluation of nursing by interviewing the patient and family, observation, physical examination, record the development of the medical record patient, some books and journal literature. The case studies conducted in the Parang Seling RSOP Soeharso Surakarta on March 28th, 2016 to April 2th, 2016. The results showed significant changes after practice a deep breath, this is evidenced by the results on the second day and third day with the final result of evaluation respiratory rate : 20 times per minute, and without using an accessory muscles of breathing. The conclusion is the provision of breathing exercises can reduce breathlessness and provide benefits in improving breathing patterns in patients with cervical dislocation Fracture.